Os impactos da globalização no Direito do Trabalho - Garcia, Elisabete (2016)
The scope of this work is to point out the impacts that the phenomenon globalization has had on the rights to classic work which has brought to contemporary society a global-social dynamic, conflicting between the ideal democrat, which has its core in the guarantee of fundamental rights and the economic systems. For the neoliberals, there should be from the States a downsizing of the minimum guarantees which is incompatible with the State of Social Well-Being. The protection of the worker through a legal system happened by influence of the syndicate movement, which was created to establish minimum civilized conditions so that the relation between the capital and the job can transcribe in a fair and equitable manner, besides being a strong ally so that employers act as a social transforming agent. Economy globalization is one of the main factors of social differentiation and transformation of social systems. However, it is not a process oriented only by markets or by the economy; it involves scientific, cultural, technological, logistic transformations and reorganization of the geopolitical global scenery and similarly in local politics. What is expected by the end of the present is to offer assistance so that the transition to the Right of Labor occurs in such a way that economic and social interests are contemplated, however, without retroacting social conquests thus reached, that represent a minimum level of civility whose norms are universally accepted and recognized by the ILO, which is the summit of International Right of Labor in all the world